Delayed Development of Coronary Ostial Stenosis following Surgical Aortic Valve Replacement: A Case Report of Unusual Presentation - Doosup Shin; Kevin Huang; Igor Sunjic; Michael Berlowitz; Xavier Prida (Case Reports in Cardiology)
Coronary ostial stenosis is a rare but potentially life-threatening complication that occurs in 1%–5% of patients who undergo surgical aortic valve replacement (SAVR). Symptoms typically appear within the first 6 months and almost always within a year after SAVR. We report an unusually delayed presentation of non-ST segment elevation myocardial infarction due to coronary ostial stenosis 22 months after SAVR. A 71-year-old woman underwent uncomplicated SAVR with a bioprosthetic valve in August 2015 for severe aortic stenosis. A preoperative coronary angiogram demonstrated widely patent left and right coronary arteries. In June 2017, the patient presented to the hospital with chest pain. An electrocardiogram demonstrated 1 mm ST segment depression in the anterolateral leads, and serum troponin I level was elevated to 2.3 ng/ml. Diagnostic coronary angiography revealed severe ostial stenosis (99%) of the right coronary artery. A bare-metal stent was successfully placed with an excellent angiographic result, and the patient was asymptomatic at 4 months of follow-up after the procedure. As seen in our case, coronary ostial stenosis should be considered in the differential diagnosis of chest pain or arrhythmia in patients presenting with a history of SAVR, even if the procedure was performed more than 1 year prior to presentation.